Implementing patient-centred care in the context of an integrated care program. (December 2015) - Cooper, Helen; McMurray, Anne; Ward, Lauren; Connor, Martin
The patient-centred or 'partnership' approach to delivering care is widely acknowledged as a key feature of high-quality health care systems. The aims of patient-centred care are to encourage people to become active participants in health care decisions, and to act in partnership with them in a way that is respectful of and responsive to their needs, values and preferences. Integrated systems offer an ideal platform to optimise patient-centred care, given their focus on structures and processes that position patients at the centre, rather than the margins of health decision making. The Gold Coast Integrated Care program in Queensland, Australia, embodies the patient-centred approach in providing an alternative to hospital-centric services and better coordination of care for those with complex and chronic conditions. Multidisciplinary teams based in a Coordination Centre collaborate with the patient and primary care practitioner (General Practitioner) to undertake a holistic assessment of needs and risks that are managed and monitored through a shared health information system. This model is transformative for future services in enabling patient-centred, cost-effective, reliable and robust care for those with complex and/or chronic diseases.